Production of Activated Carbon from Sifted Coke and Determination of Its Physicochemical Characteristics - Aigul T. Ordabaeva; Zainulla M. Muldakhmetov; Arstan M. Gazaliev; Sergey V. Kim; Zhazira S. Shaikenova; Mazhit G. Meiramov (Molecules, 2023)
The possibility of obtaining effective coal sorbents from a low-liquid product of coke chemical production—coke fines—has been studied. To obtain a coal sorbent, coke fines with a size of ≤10 mm were crushed and sieved to obtain a fraction of 2–5 mm. The resulting fraction was activated in a specially designed reactor at 850 °C with steam treatment. Activation was carried out at different durations of the process: 60, 90, and 120 min. It was found that the sample obtained with a process duration of 120 min has the best indicator for the ability to remove phenol from aqueous solutions (74.94 mg/g) and methylene blue (145 mg/g). When cleaning tap water with the resulting carbon sorbent, there is a decrease in the content of calcium, sulfates, and bicarbonate and a decrease in total mineralization. Obtained activated carbon was studied by scanning electron microscopy, low-temperature nitrogen adsorption (BET), and FTIR spectroscopy. It was found that the resulting activated carbon has a porous structure consisting of meso- and macropores, and the specific surface value was ~301 m2/g. The presence of high-intensity absorption bands corresponding to acid functional groups has also been established.